Analisis Struktur Modal Dalam Meningkatkan Laba Pada PT. Bekasi Asri Pemula,Tbk Yang Terdaftar di Bursa Efek Indonesia (2008-2012) - Nova Suhendra; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study is : ( 1 ) To determine and analyze the structure of capital employed and ( 2 ) To identify and analyze the profit obtained PT Bekasi Asri Beginners , Tbk . This research was conducted in the office place IDX obtain data which is located at Jenderal Sudirman street number 73 Pekanbaru.The method used is descriptive quantitative . With the object of research is PT Bekasi Asri Pemula,Tbk, which has been listed on the Indonesia Stock Exchange . With this method of data collection by means of documentation of financial reporting period 2008-2012 . Data analysis techniques using Debt Ratio ( DR ) , Debt Equity Ratio ( DER ) and the Times Interest Earned ( TIE ) to measure the capital structure and Return On Investment (ROI) to measure the earnings of the company.With the results of this study is that capital structure measured by DR, DER, TIE good and will be good for the company to increase profits as measured by ROI .Keywords : Capital Structure, Profitability, Return on Investment